1994
DOI: 10.1038/bjc.1994.218
|View full text |Cite|
|
Sign up to set email alerts
|

Subcutaneous low-dose recombinant interleukin 2 and alpha-interferon in patients with metastatic renal cell carcinoma

Abstract: A double-institution phase II study was performed in patients with metastatic renal cell carcinoma treated subcutaneously (s.c.) with interleukin 2 (IL-2) and alpha-interferon (INF-alpha). Thirty-eight patients were treated over a course of 7 weeks. Initially (day 1 + 2) patients received s.c. IL-2 at 18 x 10(6) IU m-2. During the following 6 weeks, patients received s.c. IL-2 at 3.6 x 10(6) IU m-2 for 5 days per week and s.c. INF-alpha at 5 x 10(6) for 3 days per week. Thirty-eight patients were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 17 publications
(27 reference statements)
0
16
0
Order By: Relevance
“…As first-line treatment, IFNa and IL-2 have shown objective responses in 18% of patients included into trials that we conducted Ravaud et al, 1994); we planned to detect a response rate X10%. We assessed the response rate after 29 patients had been recruited to have a 95% chance of detecting at least one response when the actual response rate was X10%.…”
Section: Discussionmentioning
confidence: 99%
“…As first-line treatment, IFNa and IL-2 have shown objective responses in 18% of patients included into trials that we conducted Ravaud et al, 1994); we planned to detect a response rate X10%. We assessed the response rate after 29 patients had been recruited to have a 95% chance of detecting at least one response when the actual response rate was X10%.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been performed to improve the results and/or reduce treatment-related toxicity. In both experimental tumour models and human cancer patients it has been shown that S.C. or regional IL-2 administration results in better tolerance of the treatment without apparent loss of therapeutic efficacy (Ottow et al, 1987;Steis et al, 1990;Vaage, 1991;Sleijfer et al, 1992;Ravaud et al, 1994;Sone and Ogura, 1994). Also, evidence is accumulating that doses of less than 10% of the maximum tolerated dose are therapeutically effective (Cortesina et Bruton and Koeller, 1994;Yang et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The median duration of a partial response (PR) is 12-19 months. Combinations of IFN-α and IL-2 show the same response rates as both cytokines alone [23][24][25][26][27][28][29]. In a large phase III study no survival benefit was detected for patients being treated with the combination as compared to both cytokines alone [22].…”
Section: Introductionmentioning
confidence: 95%